2009
DOI: 10.2320/matertrans.mra2008301
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of the Composition and Size of Oxide Particles in Solid Materials by Laser Ablation-Inductively Coupled Plasma Mass Spectrometry

Abstract: Laser ablation-inductively coupled plasma mass spectrometry (LA-ICP-MS) has been used for the determination of the composition and size of oxide particles consisting of SiO 2 , MnO, Al 2 O 3 , MgO and CaO on the surface of a glass or metal sample. The composition and size of multicomponent oxide particles such as MnO-SiO 2 , CaO-Al 2 O 3 and CaO-Al 2 O 3 -MgO evaluated by LA-ICP-MS are compared with those obtained by chemical analysis and by SEM observation. It is confirmed that LA-ICP-MS method has prospects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…The inclusion characteristics in metal such as composition, size and number were analyzed on polished cross section of samples by LA-ICP-MS. A schematic illustration of LA-ICP-MS system, general instrumental conditions and analytical procedures were described in previous articles. 7,10,14) The samples (Exp. 1-8 in Table 1), standard metal samples (LSt-1 to LSt-6 in Table 2) and glass standard samples (SBL-0 to SBL-5) were measured using LA-ICP-MS at the same operating parameters: laser scan speed = 0.01 mm/s, laser energy = 2.0 mJ/shot, laser shot frequency = 20 Hz and defocus of laser beam = 0 mm.…”
Section: La-icp-ms Measurementmentioning
confidence: 99%
See 3 more Smart Citations
“…The inclusion characteristics in metal such as composition, size and number were analyzed on polished cross section of samples by LA-ICP-MS. A schematic illustration of LA-ICP-MS system, general instrumental conditions and analytical procedures were described in previous articles. 7,10,14) The samples (Exp. 1-8 in Table 1), standard metal samples (LSt-1 to LSt-6 in Table 2) and glass standard samples (SBL-0 to SBL-5) were measured using LA-ICP-MS at the same operating parameters: laser scan speed = 0.01 mm/s, laser energy = 2.0 mJ/shot, laser shot frequency = 20 Hz and defocus of laser beam = 0 mm.…”
Section: La-icp-ms Measurementmentioning
confidence: 99%
“…1(b). Since the ion intensity of isotope is directly proportional to the mass of this element in ablated inclusion, 7,14) it can be concluded that the maximum size of inclusions in sample Exp. 5 is larger than that in Exp.…”
Section: Analysis Of Particle Size Distribution In Metalmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, methods for quick determination of inclusion characteristics are under development, i.e. OES‐PDA 1, 2 and LA‐ICP‐MS 3, 4. However, for accurate determinations of inclusion characteristics in steel samples from liquid steel, they should be homogenous and represent the conditions in the liquid steel in the ladle.…”
Section: Introductionmentioning
confidence: 99%